Perlindungan Hukum Data Pribadi di Era Globalisasi Digital: Studi Perbandingan General Data Protection Regulation Uni Eropa dengan Undang-Undang Perlindungan Data Pribadi Indonesia - Ismail Syadam Bahri (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
Personal data protection has become an increasingly important legal issue due to the rapid development of digital technology and the growing volume of personal data processing activities. Indonesia has enacted Law Number 27 of 2022 concerning Personal Data Protection (PDP Law) as the primary legal framework for personal data protection. However, several limitations remain within its substantive and institutional aspects, requiring further improvement. This study aims to analyze the substantive and institutional limitations of the PDP Law and to formulate an ideal reconstruction model for personal data protection in Indonesia by referring to the principles of the European Union’s General Data Protection Regulation (GDPR). This research is a normative legal study employing statutory, conceptual, and comparative approaches. The legal materials consist of primary, secondary, and tertiary legal sources, which are analyzed using a prescriptive legal method. The findings reveal that the substantive limitations of the PDP Law include the regulation of personal data protection principles, data subject rights, cross-border personal data transfers, and compliance and enforcement mechanisms. Institutional limitations are identified in the regulatory framework concerning supervisory authorities and the coordination of oversight mechanisms. The proposed reconstruction model includes strengthening personal data protection principles, enhancing data subject rights, improving cross-border data transfer mechanisms, developing an accountability-based compliance system, establishing a supervisory authority with functional independence, and reinforcing coordination among sectoral regulators. Such reconstruction is expected to create a more comprehensive, effective, and legally certain personal data protection system in Indonesia.